The Exploration of Factors Triggering Foreign Language Anxiety: LearnersÃ¢â¬â¢ Voice - Ardi Marwan (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
This article presents the findings of a study looking at the factors which learners believe have contributed to their anxiety in their foreign language learning. A questionnaire with a three-point Likert scale was developed and used as the means for data collection. Descriptive analysis of the data, focusing on mean scores, was carried out using SPSS software. The results indicate that most learners experienced foreign language anxiety in their learning. Factors such as lack of preparation, lack of confidence and fear of failing the class have been the major contributors to learners fo-reign language anxiety.